A manual for writers of term paper, theses y and dissertations - Turbian, Kate L (The University of Chicago Press / Chicago, 1996)
Contents: Parts of the paper; Abbreviations and numbers; Spelling and puntuation; capitalization, Italics, and quotation marks; Quotations; Tables; Ilustrations; notes